SURVIVORSHIP OF THE IMMATURE STAGES OF ANOPHELES CULICIFACIES IN DAMAN DISTRICT, BALUCHISTAN, IRAN - B. Davari; M.Zaim; M.Nateghpour (Tehran University of Medical Sciences, 1994)
Survivorship of the immature stage of Anopheles culicifacies in Damar District were studied through sampling larval and pupal stages from stream bed pools and rice fields during May and August 1993. The duration of each larval instar and the pupal stage was also determined in the laboratory for preparing the survivorship curves and the construction of the life tables. Mortality from egg to adult stage was estimated as 86% and 78% in stream bed pools and rice fields, respectively. The highest mortality rate in stream bed pools occurred in 4th instar larvae (61%), whereas in rice fields the highest mortality rate was observed in pupal stage (45%). Expectation of life for the newly emerged larvae in stream bed pools and rice fields were estimated 6.04 and 7.04 days, respectively. The density and fauna of predators were richer in stream bed pools as compared to that of rice fields.